Trends in Clinical Pharmacist Integration in Family Medicine Residency Programs in North America - Jennie B. Jarrett; Jody L. Lounsbery (MDPI AG, 2020)
(1) Objective: To determine the change in prevalence of clinical pharmacists as clinician educators within family medicine residency programs (FMRPs) in North America and to describe their clinical, educational and administrative scope over time. (2) Methods: A systematic review of the literature was performed starting with an electronic search of PubMed and Embase for articles published between January 1980 and December 2019. Studies were included if they surveyed clinical pharmacists regarding their clinical, educational, or other roles in FMRPs in the United States or Canada. The primary outcome was the change in prevalence of clinical pharmacists in North America. Secondary outcomes included: demographic information of clinical pharmacists, change in the prevalence in Canada and United States, and descriptions of clinical services, educational roles, and other activities of clinical pharmacists within FMRPs. (3) Results: Of the 65 articles identified, six articles met the inclusion criteria. The prevalence of clinical pharmacists as clinician educators in FMRPs in North America has grown from 24% to 53% in the United States (U.S.) and from 14% to 47% in Canada over the study period. The clinical and educational roles are similar including: the direct patient care, clinical education, and interprofessional education and practice. (4) Conclusion: The prevalence of clinical pharmacists in FMRPs is growing across North America. Clinical pharmacists are highly educated and trained to support these clinician educator positions. While educational roles are consistent, clinical pharmacists' patient care roles are unique to their clinical site and growing.